Career options - Sheahan, Peter; Lovering, Matthew (Bendigo, Victoria : Video Education Australasia, 2003)
Summary: In this program, Peter shares a fun and practical way for students to research their career options. It also focuses on subject selection and study selection beyond school. It is a fun, inspiring and informative program.
Executive producer, Mark McAuliffe ; editor, Jarred Marshall
Speaker: Peter Sheahan
Keywords: Job descriptions; Occupations